Konsep Pembangunan Hukum dan Perannya Terhadap Sistem Ekonomi Pasar - Dhaniswara K. Harjono (Fakultas Hukum Universitas Islam Indonesia, 2011)
The issues in this study include:1) Is the implementation of market economic system run properly and 2) What contribution does law give in market economic and what concept of a pro-market Law Development should be. Conducted by using the judicial-normative method and specified by an analytical-descriptive approach, this research is aimed to obtain the secondary data through a library research for the substances relevant to legal materials on the theories about laws and economics, which at this point is by using a qualitative analysis. The research then concludes that the system of market economy refers to the one giving freedom to individual to achieve as high profit as possible in the economic aspect. There is no role of government as all economic system is given to the individual as the subject of economy. Nevertheless, the market economy is not able to be fully conducted without involving the government that in this case acts to regulate the law. Without this, a downturn of market economy will occur. The system of market economy without any legal support, particularly economic law, will never properly run to achieving the welfare and prosperity.